Artificial Intelligence Helps Protect Smart Homes against Thieves - Pala, Zeydin; Özkan, Orhan (My University, 2020)
Interaction with the environments in which humans live is increasing more and more, andArtificial Intelligence (AI) offers significant contributions to this. Although the topic of smarthomes has attracted a great deal of attention from researchers, the AI-based application in thisarea is still in its infancy. In this study, a home security automation system, which is quitesimple, but smart and AI-based, is proposed. When the home-dwellers were not at home, thehome lighting system tried to be managed with AI at night, as if life was still there. The AIbased smart home physical design was done using Arduino equipment and was tried to beadapted to the real-life environment with software support. As if there was someone at home,a special dataset, which was consisted of nine inputs, one output vector and about 5500 sampleswas created to turn on/off the home lights in a manner suitable for night life. The home lightingsystem was successfully managed using an AI-based system that learns nightlife lightinghabits.The proposed system performance was tested in support of commonly used machine learningclassification algorithms such as Multi-layer perceptron (MLP), Linear support vector machine(L-SVM), Gaussian Naive Bayes (NB), and linear discriminant analysis (LDA). The accuracyvalues of MLP, L-SVM and NB algorithms were 96.69%, 94.98% and 91.23%, respectively.Our results show that a home with AI could be safer and more secure against theft.